Gait retraining using visual and verbal feedback in runners - Gray, E.; Sweeney, M.; Creaby, M.; Smith, M. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Overuse injuries occur when the body is exposed to large magnitudes of repetitive forces such as those applied during to the body during running. Differences in running style have been found to modify impact forces and related shock applied to the lower extremity, having the ability to increase or decreasing the potential risk of injury. To date research has indicated that gait retraining biofeedback has a positive influence on both reducing injury factors as well as aiding in the rehabilitation of already injured athletes (Crowell & Davis, 2011; Crossley et al, 2010; Tate & Milner, 2010). However, an optimal biofeedback protocol within gait retraining remains unclear.